1994
DOI: 10.1007/bf00374529
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ca2+ oscillations by selective, U73122-mediated, depletion of inositol-trisphosphate-sensitive Ca2+ stores in rabbit pancreatic acinar cells

Abstract: The effect of the putative inhibitor of phospholipase C activity, U73122, on the Ca2+ sequestering and releasing properties of internal Ca2+ stores was studied in both permeabilized and intact rabbit pancreatic acinar cells. U73122 dose dependently inhibited ATP-dependent Ca2+ uptake in the inositol (1,4,5)-trisphosphate-[Ins(1,4,5)P3]-sensitive, but not the Ins(1,4,5)P3-insensitive, Ca2+ store in acinar cells permeabilized by saponin treatment. In a suspension of intact acinar cells, loaded with the fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Stimulation of the purinoceptors activated PLC, since the ATP-induced increase in [Ca21], could be inhibited by the aminosteroid U73122, which has been shown to inhibit a variety of PLC mediated events (Smallridge et al, 1992;Vickers, 1993;Jin et al, 1994;Willems et al, 1994;Gromada et al, 1995a). The responses to UTP and 2MeSATP were also abolished by U73122 indicating that both P2y-and P2u-receptors couple to PLC.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation of the purinoceptors activated PLC, since the ATP-induced increase in [Ca21], could be inhibited by the aminosteroid U73122, which has been shown to inhibit a variety of PLC mediated events (Smallridge et al, 1992;Vickers, 1993;Jin et al, 1994;Willems et al, 1994;Gromada et al, 1995a). The responses to UTP and 2MeSATP were also abolished by U73122 indicating that both P2y-and P2u-receptors couple to PLC.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that, in addition to PLC inhibition, U-73122 depletes internal Ca 2ϩ stores (Jin et al, 1994;Willems et al, 1994). Although this has to be confirmed in astrocytes, such a side effect of U-73122 does not rule out the role of PLC and IP 3 in intercellular calcium signaling.…”
Section: Plc Activation Is a Necessary Step For Regenerative Intercelmentioning
confidence: 98%
“…U73343, the inactive analogue of U73122, had no significant effect upon the release of Ca 2 þ (P40.05, n ¼ 18). A dose of 1 mM U73122 was not exceeded as this compound has been shown to release Ca 2 þ from internal stores at higher doses (Willems et al, 1994;Mogami et al, 1997;Jan et al, 1998 ( Figure 4a). These results suggest that the observed WIN55,212-2-mediated Ca 2 þ mobilization did not depend on CB 1 -G i/o coupling.…”
Section: Cb 1 Expression In Htm Cellsmentioning
confidence: 99%